Towards enabling accurate measurements of CO2 exposure indoors. (1st April 2022) - Kierat, Wojciech; Ai, Zhengtao; Melikov, Arsen; Markov, Detelin; Bivolarova, Mariya
Abstract: Indoor climate standards recommend maximum CO2 concentration levels in rooms. At present the CO2 exposure of occupants is assessed by measurements in a room's exhaust air or near the walls. However, most often room air is not perfectly mixed and CO2 emitted in air exhaled by occupants is non-uniformly distributed. It is more reliable to assess CO2 concentration in the air inhaled by occupants by measurements in the breathing zone as close as possible to the face. In this work the importance of the location of air sampling in front of the face, the time and frequency of sampling, and the breathing mode, for the accuracy of CO2 measurements were studied. For this a breathing thermal manikin was used. The CO2 concentration in the air exhaled by the manikin was adjusted to be the same as that for an average person. The results show that synchronization of the air sampling with the inhalation period of breathing is the most accurate method. The air sampling locations positioned between the centre of the chin and the mouth, or at the left (or right) corner of the mouth, or next to and above the nostrils, are the most representative for assessing CO2 concentration in the inhaled air. The obtained results can be used for the development of wearable devices for accurate assessment of exposure to CO2 and other indoor pollution, as well as advanced air distribution methods, such as personalized ventilation that supplies clean air to the breathing zone. Highlights: The most representative sampling locations for CO2 exposure assessment were proposed. Gas sampling synchronized and unsynchronized with inhalation phase were compared. The synchronized sampling method was found to be the most accurate method. The measured CO2 concentration was independent from the breathing mode.